2024
DOI: 10.1021/acssusresmgt.3c00064
|View full text |Cite
|
Sign up to set email alerts
|

Waste Iron Dust Derived Iron Oxide Nanoparticles for Efficient Adsorption of Multiple Azo Dyes

Twinkle,
Hema Tewatia,
Jaidev Kaushik
et al.

Abstract: Herein, we have described a simple and viable approach to use the waste byproduct of steel industries: red iron oxide dust (IOD) for synthesizing its reduced version as reduced-IOD (r-IOD). The r-IOD possess active multiphases of iron oxides (Fe@Fe3O4@Fe2O3) and is used for the adsorption of three organic dyes. The surface area of magnetically active r-IOD is found to be ∼4.5 times than that of IOD and shows better mesoporosity. Due to having a larger surface area, r-IOD is used for the efficient adsorption of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…It was found that only in the presence of r-IOD and NaBH 4 nitrophenols were successfully reduced to their corresponding products (∼99% PAP, ∼53% DAP, and ∼78% TAP), as shown in Figure e. The better reduction catalytic ability of r-IOD than that of IOD can be due to the presence of a higher surface area (better textural properties) and multiple active Fe-oxide phases. Further, various batch studies were performed to optimize the reaction conditions such as concentration of the reactant, catalyst loading, and the amount of reducing agents.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…It was found that only in the presence of r-IOD and NaBH 4 nitrophenols were successfully reduced to their corresponding products (∼99% PAP, ∼53% DAP, and ∼78% TAP), as shown in Figure e. The better reduction catalytic ability of r-IOD than that of IOD can be due to the presence of a higher surface area (better textural properties) and multiple active Fe-oxide phases. Further, various batch studies were performed to optimize the reaction conditions such as concentration of the reactant, catalyst loading, and the amount of reducing agents.…”
Section: Resultsmentioning
confidence: 90%
“…The r-IOD was synthesized using the previously reported methods, and discussed in the Experimental Section (see Supporting Information). The morphological changes observed after the chemical reduction process were analyzed by field emission scanning electron microscopy (FESEM) and high-resolution transmission electron microscopic analysis (HRTEM). The low-resolution FESEM image in Figure a displayed the spherical morphology of IOD particles, and Figure b showed FESEM image of r-IOD particles having flake-like morphology, which can also be seen in the low-resolution TEM image of r-IOD in Figure c showing significant morphological changes after the process of chemical reduction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations